Effectiveness Of Management Of Terminal Services Type A Latenrisessu Pekkae In Realizing Order At Terminals In Barru Regency - Muliana; Rezky Nur Padhilah (P3M Stia Al Gazali Barru and Meraja media, 2025)
[Full Paper] to pdf Copyright (c) 2025 Meraja journal